Experimental Findings and Clinical-Pathologic Correlation of Radiofrequency Catheter Ablation at the Left Ventricle Para-Hisian Region - Fu, Zuyi; Liao, Zili; Zhang, Jinlin; Zhan, Xianzhang; Lin, Weidong; Liu, Fang Zhou; Su, Xi; Deng, Hai; Fang, Xianhong; Liao, Hongtao; Wang, Hongyue; Wu, Shulin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Catheter ablation target at the site with large His activation in the left ventricle poses a high risk of atrioventricular (AV) block. We aimed to identify far-field (FF) and near-field (NF) His activation at left upper septum (LUS). Methods: Three-D mapping of the aortic root and left ventricle was performed in 12 dogs. Two sites located at either the base or apex of the triangle interposed between the hinges of the the noncornary coronary cusp (NCC) - right coronary cusp (RCC) were chosen for a single radiofrequency (RF) application. Bipolar and unipolar pacing with different outputs at both sites was attempted to discern NF and FF His activation. Results: The sites chosen for NF and FF ablation were located at the base and apex of the triangle, which were 8.03±1.18mm (group 1) and 3.42±0.61mm (group 2) away from the RCC-NCC junction. Lower A/V ratios were found in group 1. Pacing could not differentiate NF from FF His activation. In group 1, ablation resulted in III degree AV block in all 6 dogs, whereas neither PR prolongation nor AV block occurred in group 2. Pathologic examination of group 1 showed complete/partial necrosis of the His bundle (HB) and left bundle branch in all 6 dogs. In group 2, no necrosis of the HB was seen in the 6/6 dogs. Conclusion: Anatomical localization in the triangle of RCC-NCC junction can help differentiate NF from FF His activation.